LEGAL ANALYSIS OF THE LIMITED LIABILITY COMPANY NAME CHECK SYSTEM THROUGH ONLINE GENERAL LEGAL ADMINISTRATION - Rr. Ayu Gayatri Esa Prameswari; Benny Djaja; Maman Sudirman (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2024)
A Limited Liability Company (LLC) is gaining popularity within various business circles as a legal entity consisting of directors, commissioners, and shareholders. Establishing an LLC requires adherence to specific requirements and procedures to obtain legal documents, with evidence and manifestation of legality aspects presented, registered, and ratified by the Directorate General of Law and Human Rights through the online system. Formally, the deed for LLC establishment must be drafted in Indonesian by at least two individuals, meeting the material requirements specified in Article 9 of Law Number 40 of 2007 concerning Limited Liability Companies. The procedure for creating a Deed of Establishment by a notary is governed by Article 39 of Law Number 2 of 2014 concerning the Position of Notaries, involving presenters approaching the notary, verification of the name, signing of the deed, registration with the relevant Ministry, and issuance of a Legal Entity Decree. Notaries may encounter obstacles, including technical issues like system inaccessibility, addressed through communication with AHU Online (Online General Legal Administration), and non-technical issues resolved through improvements. Responsibility for material truth lies in the validity of the deed, while responsibility for formal truth involves adherence to statutory regulations in the deed-making process.